EXCITATION AND INHIBITION PROCESSES IN THE CENTRAL NERVOUS SYSTEM (Journal of Universal Science Research, 2026)
This article analyzes in detail the mechanisms of excitation and inhibition, which are the main physiological processes of the central nervous system. The central nervous system is a complex biological system that controls the activities of all organs and systems in the human body and ensures their mutual coordination